Bahasa Tansi: The Language Loyalty of Its Speakers - Rahayu, Sabila; Jufrizal, Jufrizal (Universitas Negeri Padang, 2024)
The aim of this study was to determine the degree of language loyalty of bahasa Tansi speakers in Sawahlunto, West Sumatra, through a sociolinguistic analysis focusing on lexical differences, language loyalty, and language attitudes. This quantitative and descriptive qualitative research examined whether bahasa Tansi speakers are loyal in using the language or not. Data were collected using the 206 of Swadesh list words, questionnaires, interviews, and recorded conversations. The findings revealed that bahasa Tansi has 73.78% phonetic differences compared to Minangkabau, suggesting significant language divergence. Additionally, the study highlighted a strong sense of language loyalty and positive attitudes among speakers, indicating bahasa Tansi's robust sociolinguistic presence. Consequently, bahasa Tansi is classified as a creole with unique linguistic and cultural attributes, contributing to the linguistic diversity of West Sumatra.